City of saints - Hunt, Andrew E., 1968- (Minotaur Books, 2012)
A historical mystery set in 1930s Salt Lake City finds a rookie investigator and Mormon family man partnering with a foul-mouthed, vice-ridden former strikebreaker to solve the murder of a beautiful socialite.